2002
DOI: 10.1029/2001jd000477
|View full text |Cite
|
Sign up to set email alerts
|

Observations and analysis of polar stratospheric clouds detected by POAM III during the 1999/2000 Northern Hemisphere winter

Abstract: We present an overview of polar stratospheric cloud (PSC) measurements obtained by POAM III in the 1999/2000 Northern Hemisphere winter. PSCs were observed at POAM latitudes from mid‐November to 15 March. PSCs in the early season generally occurred between 17 and 25 km. The central altitude of the PSC observations, roughly 21 km, is unchanged between November and late January. PSCs were not observed between 7 and 27 February. When they reappeared, they formed at distinctly lower altitudes, centered roughly at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 38 publications
(86 reference statements)
2
33
0
Order By: Relevance
“…In general however, there are not enough data to draw consistent conclusions on formation mechanisms. On the other hand, there are a wealth of sightings of polar stratospheric clouds by satellite [ McCormick et al , 1982; Poole and Pitts , 1994], and more recent data from the POAM instruments [ Fromm et al , 1997, 1999; Bevilacqua et al , 2002]. Unfortunately these optical measurements are horizontally averaged over the transmission path, in addition to which accurate concurrent and collocated temperature data are generally unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…In general however, there are not enough data to draw consistent conclusions on formation mechanisms. On the other hand, there are a wealth of sightings of polar stratospheric clouds by satellite [ McCormick et al , 1982; Poole and Pitts , 1994], and more recent data from the POAM instruments [ Fromm et al , 1997, 1999; Bevilacqua et al , 2002]. Unfortunately these optical measurements are horizontally averaged over the transmission path, in addition to which accurate concurrent and collocated temperature data are generally unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…Observations of the vertical distribution of ozone come from the NASA Stratospheric Aerosol and Gas Experiment (SAGE) III instrument aboard the METEOR-3M satellite (Thomason and Taha, 2003), and from the NRL Polar Ozone and Aerosol Monitoring (POAM) III instrument aboard the CNES SPOT-4 satellite (Bevilacqua et al, 2002). Both satellites operate in sun-synchronous orbits that offer good coverage of polar latitudes during winter.…”
Section: Satellite Ozone Measurementsmentioning
confidence: 99%
“…Thus it seems justifiable to interpret the Arctic PSC probabilities in Figure 10b as evidence of denitrification and substantial interannual variations thereof. Winters with low January PSC probability would have probably experienced relatively large occurrences of NAT particle clouds during and/or before January, according to Bevilacqua et al [2002].…”
Section: Arcticmentioning
confidence: 99%
“…The PSC probability in 2000 is the third lowest in Figure 10b, nearly at the 1s level. Bevilacqua et al [2002] performed a detailed analysis of Arctic 2000 POAM III PSC data in terms of temperature and concluded that denitrification of the order of 75% occurred in the Arctic in 2000, with an onset in January. Strawa et al [2002] used an analysis of POAM III data to partition Arctic 2000 PSCs into solid and liquid types, finding strong evidence (as did Fahey et al [2001] and Voigt et al [2000]) for extensive solid particle PSC formation.…”
Section: Arcticmentioning
confidence: 99%